Effect of Er, Cr:YSGG laser enamel etching with varying power output and irradiation time on the shear bond strength - Saravana Kumar Subramanian; Prema Anbarasu; R S Joushua; Yamini Jeyaraj; Sushmitha R Iyer; Nivethitha Bhaskar (Journal of Orthodontic Science, 2022)
BACKGROUND: Laser etching addresses the disadvantages of conventional acid etching technique, such as enamel decalcification and formation of white spot lesions. The aim of the present study was to evaluate and compare the shear bond strength (SBS), adhesive remnant index (ARI), and the surface characteristics of the samples treated with conventional acid etching and Er, Cr: YSGG laser etching with variable output power and time durations. METHODOLOGY: The study sample included 78 extracted teeth divided into six groups of 13 teeth each, and 3 samples from each group were utilized for analyzing etch patterns, and the remaining 10 teeth from each group were used for evaluating the shear bond strength. In Group I phosphoric acid etching was done, whereas in Group II– VI Laser etching 1.5 W/10 s, 1.5 W/15 s, 3 W/5 s, 3 W/10 s, 3 W/15 s. Statistical analysis for shear bond strength testing was performed using one-way ANOVA followed by Post HOC tests. RESULTS: The mean shear bond strength of Group I was 7.16 Mpa and Group III of 5.43 Mpa. Group II, IV, V, and VI had mean shear bond strength of 4.93 Mpa, 3.88 Mpa, 4.05 Mpa, and 4.88 Mpa, respectively. The ARI scores Group I had a significant number of samples with scores 2 other groups showed increased Score 0. The etch pattern of groups I, II, III showed the combined dissolution of both prism cores, and peripheries were seen. In group IV, the etching pattern was irregular with the pitted type of surface. In groups V and VI, relatively flat and smooth enamel surface was seen. CONCLUSION: The bond strength attained by laser etching (1.5 W/10 s and 1.5 W/15 s) was comparable to that obtained by the acid etching technique.